Islamic Guidelines for Promoting Religious Tolerance and Countering Intolerance - Nasrulloh, Muhammad; Ermawan, Mohamad Zakky Ubaid; Syuhadak, Faridatus; Zubair, Muhammad Muizzuddin (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2024)
Abstract This article focuses on two issues. The first issue is the stagnation of the national tolerance score, indicating that intolerant activities continue to affect the nation. Second, the concept of tolerance is ambiguous, making it difficult to implement religious moderation. The discordance of tolerance between theory and practice is shown by these two issues. The research method in this paper utilizes a literature-based study with a conceptual approach and descriptive analysis. The conceptual approach involves examining and defining key ideas and theoretical frameworks relevant to tolerance and religious moderation, clarifying abstract concepts and underlying principles. Descriptive analysis systematically describes and interprets existing data from previous studies and literature on the topic. This research provides a framework for fostering religious tolerance based on Islamic principles, offering practical solutions to address intolerance. The framework emphasizes replacing verbal and physical harassment with supportive and cooperative actions. It also outlines strategies for turning destructive behaviors, such as the demolition of places of worship, into constructive efforts like aiding in their restoration and rebuilding. This framework aims to foster religious moderation and harmony through actionable, normative measures.